FR2.1: Improving agricultural value chain coordination and gender inclusiveness in Papua New Guinea - Kosec, Katrina; Schmidt, Emily; Carrillo, Lucia; Peixun Fang; Ivekolia, Mark; Ovah, Raywin (International Food Policy Research Institute, 2022)
In this study, we analyzed three key value chains in Papua New Guinea—poultry, sweet potato, and fresh vegetables—aiming to draw out information on women's involvement in various nodes within each value chain, as well as the barriers women typically face to benefiting fully from participation at various nodes. Using the 2018 Papua New Guinea Rural Household Survey on Food Systems (RSFS) datasets, we then investigate whether and how particular norms related to women's economic participation are influencing their employment and entrepreneurship outcomes. Our strategic review of the literature reveals that women are heavily involved in all three value chains, but more so in production and sales than in (often lucrative) mid-stream nodes—often due to barriers on their mobility, access to market information, and education and skills. Empirical analysis suggests that women's economic participation (especially their operation of non-farm enterprises (NFEs) and engagement in sales jobs and in commercial farming) is associated with greater participation of women in household decision-making and improvements in household welfare. Gender norms opposing women's economic participation, however, decrease the likelihood of women informing household decision-making – particularly for the case of women's ownership of NFEs. The results provide a strong business case for alleviating norms keeping women out of certain activities and more generally expanding opportunities for women's participation in key value chains in the agriculture and livestock sectors in PNG. This study is meant to guide policymakers and stakeholders toward ways of improving economic opportunities and inclusiveness in the agriculture and livestock sectors.